Transformation or evolution?: Education 4.0, teaching and learning in the digital age. Issue 1 (1st January 2020) - Bonfield, Christopher Alan; Salter, Marie; Longmuir, Alan; Benson, Matthew; Adachi, Chie
ABSTRACT: This paper, originally written just before the outbreak of COVID-19, will provide a review of Education 4.0 in a select range of UK and international higher education providers and offer an initial discussion of the role and importance of digital personal assistants and online and lifelong learning in delivering world-class learning and teaching. This has been validated through a literature review and four case studies using scenario-planning methodology which draw on real-world examples from the UK (University of Bath), Singapore (Nanyang Technological University) and Australia (Deakin University). What can the sector learn from these pioneers; are there opportunities still to be explored; and what impact might this have on how educators teach and deliver their curriculum in the future?